1988
DOI: 10.2307/3430516
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Pathogenesis of Pneumoconiosis in Coal Workers

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. The National Institute of Environmental Health Sciences (NIEHS) and Brogan & Partners are collaborating with JSTOR to digitize, preserve and extend access to Environmental Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…This was shown by Gough and Heppleston many years ago,'7 18 and has subsequently been confirmed by the US Public Health Service studies which showed that simple CWP in nonsmokers was associated with an increase in the residual volume and total lung capacity and in some instances with a slight to moderate loss of elastic recoil. '920 Furthermore, Hankinson and colleagues, who were working in the Appalachian Laboratory for Occupational Lung Disease (ALFORD) at the same time showed that simple CWP was associated with an increase in air space size.2' These workers were, however, unable to demonstrate that the increased size was associated with a reduction in ventilatory capacity.…”
Section: Discussionmentioning
confidence: 67%
“…This was shown by Gough and Heppleston many years ago,'7 18 and has subsequently been confirmed by the US Public Health Service studies which showed that simple CWP in nonsmokers was associated with an increase in the residual volume and total lung capacity and in some instances with a slight to moderate loss of elastic recoil. '920 Furthermore, Hankinson and colleagues, who were working in the Appalachian Laboratory for Occupational Lung Disease (ALFORD) at the same time showed that simple CWP was associated with an increase in air space size.2' These workers were, however, unable to demonstrate that the increased size was associated with a reduction in ventilatory capacity.…”
Section: Discussionmentioning
confidence: 67%
“…A basic comment on our approach would also be that, although mechanisms of quartz-and coal dustinduced fibrosis are similar, distinct pathological differences are present between simple pneumoconiosis and silicosis (Heppleston, 1988). However, it is unknown whether this difference is relevant to the total lung burden of quartz and its relevance to this risk assessment procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies in coal miners have indicated that the risk of dust-related disease is subject to considerable variation. The incidence of sCWP and PMF varies with countries, regions and even within horizons of mine pits (Reisner et al, 1985;Heppleston, 1988;Gautrin et al, 1994). German epidemiological studies showed that the risk of contracting sCWP between coal fields varied between 2 and 40%, although miners had comparable levels of exposure (for a review see Morfeld and Piekarski, 1998).…”
Section: Pneumoconiosis and Lung Cancer In Coal Minersmentioning
confidence: 99%
See 1 more Smart Citation
“…In Equation (1), π ij represents the risk of death from pneumoconiosis for the i th person residing in the j th county, which is explained by a set of individual and county‐level characteristics X i , and Z j , county‐specific random effects ν j , and individual random effects ε ij . We imposed zero mean identical and independent Gaussian distribution with variance σ 2 on ε ij . We considered three different models.…”
Section: Methodsmentioning
confidence: 99%